DNA sequences and morphological variation in Lophiodes iwamotoi Ho, Serét & Shao, 2011 based on new material from New Caledonia - Ho, Hsuan-Ching; Chen, Wei-Jen (Zootaxa, 2013)
Iwamoto’s anglerfish Lophiodes iwamotoi is recorded from New Caledonia for the first time. Study of molecular features further support the validity of the species. Moloecular sequence data from the cytochrome c oxidase subunit-I and Rho-dopsin loci, along with morphological variation are provided, as well as information on its fresh coloration.